2018
DOI: 10.3126/banko.v28i1.21453
|View full text |Cite
|
Sign up to set email alerts
|

Variation in structure and composition of two pine forests in Kailash Sacred Landscape, Nepal

Abstract: Chir pine (Pinus roxburghii Sarg.) and blue pine (Pinus wallichiana A.B. Jacks.) are two common species found in mid-hill forests of Nepal where households largely depend on forest resources for their livelihoods and subsistence. The management of such forests is supported by our understanding of the dynamics in forest structure and species composition and the relationship between different forest community characteristics. This study was designed to determine the variation in species composition and the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The lower altitude has lesser diversity and regeneration due to human intervention and logging activities. Subedi et al (2018) in chirpine and blue pine forest of Nepal found that when the number of disturbances increases, the diversity, and regeneration of tree decreases in the blue pine forest. The logging activities in the present study area not only reduce species diversity but also disturbs soil nutrient content through surface runoff.…”
Section: Regenerationmentioning
confidence: 98%
“…The lower altitude has lesser diversity and regeneration due to human intervention and logging activities. Subedi et al (2018) in chirpine and blue pine forest of Nepal found that when the number of disturbances increases, the diversity, and regeneration of tree decreases in the blue pine forest. The logging activities in the present study area not only reduce species diversity but also disturbs soil nutrient content through surface runoff.…”
Section: Regenerationmentioning
confidence: 98%
“…These include the estimation of biomass in Australian Eucalyptus forests [34] and Indian humid tropical forests [35], environmental assessment using tree rings in France [33], the growth response to climate change in Chinese forests [36], and carbon concerning REDD+ in Latin American countries [37]. Similarly, in Nepal, studies cover a wide range of aspects such as ecosystem services [31], carbon-to-soil properties, and REDD+ concerns [38,39]. However, there is a lack of research comparing planted and natural forests regarding ecological sustainability and biomass production potential.…”
Section: Millionmentioning
confidence: 99%
“…Research related to the ecological aspect of climate (Bajwa et al 2015), forest carbon, biomass and sequestration (Aryal, 2016), and vegetation composition have been carried out in pine-dominated forest stands in different regions (Subedi et al, 2018). Besides knowing the importance of the carbon fluxes and their vulnerability to climatic alteration, soil carbon fluxes and their susceptibility analysis in the pure P. roxburghii forest stand structure is yet lacking.…”
Section: Introductionmentioning
confidence: 99%